Pengaruh Latihan Tactical Attacking Options for Two Players terhadap Menyerang Tim Futsal Putra UNJ - Mahesa Abirezi; Andri Irawan; Uzizatun Maslikah (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
The aim of this research is to find out how much influence the tactical attacking options training for two players (vertical pairs, parallela, and backdoor) has on attacking the UNJ men's futsal team. The method used in this research is the experimental method. The population of this study were members of the UNJ Men's Futsal KOP, totaling 64 people. The sample consisted of 17 athletes who competed with proportional sampling. The design used in this research is a one-group pre- and post-test design. From the results of the tactical attacking options test, the initial test average was 3.57 and the standard deviation was 0.56. The final test average was 7.29, and the standard deviation was 1.55. From the results of the average and standard deviation, the thitung is 9.57, while the ttable with a significance level of 0.05 with df (n - 1) = 13 is 2.16. Based on the results of these calculations, it can be seen that tcount (9.57) > ttable 2.16, so H0 is rejected and H1 is accepted. This means that the tactical attacking options for the two-player exercise have an effect on improving UNJ men's futsal attacking ability..